Identifikasi Hama Pascapanen Jagung Pakan di Gudang PT. Arutmin Site Satui - Rizal, Muhammad; Pramudi, Muhammad Indar; Liestiany, Elly; Aphrodyanti, Lyswiana (www.ulm.ac.id, 2024)
Corn can be used for direct consumption, as a raw material for the food, food and bioenergy industries. As an animal feed ingredient, corn kernels that have been shelled and dried will be used to feed livestock such as chickens and ducks. However, there has been a decline in corn productivity, one of which is due to attacks by Plant Pest Organisms (OPT) in the form of pests both in the field and in storage. This research aims to determine the types of post-harvest pests of feed corn in the PT Arutmin Site Satui. This research uses a purposive sampling method. The identification results showed that there were 2 species of post-harvest pests that attacked the feed corn shells, Tribolium castaneum as many as 167 individuals and Doloessa viridis as many as 1611 individuals.